2015
DOI: 10.1021/acs.joc.5b01354
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Photoreactions of (5S)-5-Oxymethyl-2(5H)-furanones as a Tool for the Stereoselective Generation of Diverse Polycyclic Scaffolds

Abstract: The photoactivated evolution of a series of enantiomerically pure 5-oxymethyl-2(5H)-furanones has been investigated. The observed intramolecular photoreactions have proven to be a straightforward entry to diverse and stereochemically rich fragment-molecules, most of which contain the privileged tetrahydropyran (THP) scaffold. The formation of the THP involves a 1,5-hydrogen atom transfer process, leading to a diradical intermediate that recombines to form a new σ C-C bond. These reactions take place under both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…First, the intramolecular [2 + 2] photocycloaddition of 5 was investigated using experimental conditions usually applied in our laboratories for intermolecular photoreactions (Table , entry 1) . However, the irradiation of 5 in acetone through a Pyrex filter at different temperatures (from rt to −78 °C) did not afford any of the expected photoproducts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…First, the intramolecular [2 + 2] photocycloaddition of 5 was investigated using experimental conditions usually applied in our laboratories for intermolecular photoreactions (Table , entry 1) . However, the irradiation of 5 in acetone through a Pyrex filter at different temperatures (from rt to −78 °C) did not afford any of the expected photoproducts.…”
Section: Resultsmentioning
confidence: 97%
“…Our studies on the preparation of bicyclic tetrahydropyrans (THPs) by an intramolecular photoreaction of enantiomerically pure 5-oxymethyl-2­( 5H )-furanones showed that the photoreaction of lactone 1 bearing an allyloxymethyl substituent at C5 delivers mainly a regioisomeric mixture of [2 + 2] photocycloadducts 3 and 4 , along with targeted THP 2 (Scheme a) . In all of the assayed reactions, head to tail ( HT ) isomer 3 was slightly favored over head to head ( HH ) isomer 4…”
Section: Introductionmentioning
confidence: 99%
“…The same type of hydrogen abstraction was also observed in furanone derivatives carrying a benzyl or allyl moiety on the side chain. 35,40 The addition of alkoxyl and ketyl radicals to furanones in their ground state generally occurs at the β-position, as was previously discussed for α-aminoalkyl radicals. Both types of radicals are nucleophilic and their behavior therefore resembles nucleophiles in the Michael addition.…”
Section: Short Review Syn Thesismentioning
confidence: 90%
“…The same reaction was also carried out using direct excitation via light absorption of 23. 35 The re-sulting 3 ππ* state 25 is characterized by the suppression of the π-bond of the α,β-unsaturated carboxyl system. The spin density at the β-position is high while the electron at the α-position is delocalized over the carboxyl function.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Previous work has already shown that [2+2] photocycloaddition occurred with vinyl-substituted derivatives. 72 First of all, they have tested terminal alkenes with different temperatures and solvents. To achieve good yields and selectivities, acetone proved to be the best solvent at -78 °C.…”
Section: Studies Of 13-dipolar Cycloadditionsmentioning
confidence: 99%